Distortionary Taxation and the Debt Laffer Curve - Husain, Aasim (Washington, D.C. : International Monetary Fund, 1992)
This paper highlights the importance of the role of the domestic tax system in determining the economic consequences of an external debt overhang. A simple taxation scheme is specified and it is shown that a country can be on the 'wrong side' of its debt Laffer curve only if it is on the wrong side of its tax Laffer curve. The analysis indicates that fairly strong, and probably unrealistic, assumptions about the domestic tax system are needed to argue that the investment disincentives associated with the debt overhang are large enough to place a country on the wrong side of its debt Laffer curve.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Laffer Curve; WP